Intraoperative radiotherapy for glioblastoma: an international pooled analysis. (January 2020) - Sarria, Gustavo R.; Sperk, Elena; Han, Xiaodi; Sarria, Gustavo J.; Wenz, Frederik; Brehmer, Stefanie; Fu, Bing; Min, Siming; Zhang, Hongjun; Qin, Shusen; Qiu, Xiaoguang; Hänggi, Daniel; et al.
Highlights: Intraoperative radiotherapy as a boost added to the standard of care treatment is safe and feasible. Apparently, intraoperative radiotherapy for glioblastoma increases the overall survival rate (~25% at 3 years). Local failure was first progression in 35.3% of cases. No additional severe toxicity was related to this modality in comparison to conventional treatment. Abstract: Purpose: To report the results of the first international pooled analysis of patients with glioblastoma treated with intraoperative radiotherapy (IORT) in addition to standard of care therapy. Methods: Data from 51 patients treated at five centers in Germany, China and Peru were analyzed. All patients underwent tumor resection followed by a single application of IORT (10–40 Gy, prescribed to the applicator surface) with low-energy X-rays. Thereafter, standard adjuvant radiochemotherapy and maintenance chemotherapy were applied. Factors of interest were overall survival (OS), progression-free survival (PFS), local PFS (L-PFS; defined as appearance of new lesions ≤1 cm to the cavity border) and distant PFS (D-PFS; lesions >1 cm). The same endpoints were estimated at 1-, 2- and 3-years using the Kaplan-Meier method. Additionally, rates and severity (as per Common Terminology Criteria for Adverse Events Version 5.0) of radionecrosis (RN) were analyzed. Results: The median age was 55 years (range: 16–75) and the median Karnofsky Performance Status was 80 (20–100). At a median follow-up of 18.0 months (2–42.4), the median OS, PFS, L-PFS and D-PFS were 18.0 months (95% CI: 14.7–21.3), 11.4 months (95%CI: 7.58–15.22), 16 months (95%CI: 10.21–21.8) and 30.0 months (95%CI: 18.59 – 41.41), respectively. The estimated 1-, 2- and 3-year OS, PFS, L-PFS and D-PFS were 79.5%, 38.7% and 25.6%; 46.2%, 29.4%, and 5.9%; 60.9, 37.9%, and 12.6%; and 76.7%, 65.0%, and 39.0% respectively. First progression occurred locally in only 35.3% of cases. Grade 1 RN was detected in 7.8% and grade 3 in 17.6% of the patients. No grade 4 toxicity was reported and no treatment-related deaths occurred. Conclusion: Compared to historical data, this pooled analysis suggests improved efficacy and safety of IORT with low-energy X-rays for newly diagnosed glioblastoma. Prospective data is warranted to confirm these findings.